ANALISIS KADAR VITAMIN C PADA BUAH DELIMA (Punica granatum L.) MERAH DAN PUTIH SECARA SPEKTROFOTOMETRI UV-VIS - Maulana, Andi; Abidin, Zainal; Sadjidin, Sugiarto; Naid, Tadjuddin (Window of Health : Jurnal Kesehatan, 2019)
Vitamin C is one of the nutrients that act as antioxidants derived from fruits and green vegetables, such as the pomegranate (Punica granatum L.). This study aims to analisis levels of vitamin C in meat pomegranate (Punica granatum L.) red and white with qualitative and quantitative analysis. Qualitative analysis was performed using specific reagents that ammonium molybdate, Fehling Fehling's A and B which have indicated a positive sample containing vitamin C, and vitamin C were analyzed quantitatively using UV-Vis spectrophotometry at a wavelength of 570 nm. The results showed levels of vitamin C in red pomegranate fruit flesh 0.24475 mg / g and meat pomegranate 0.11577 mg / g